Effect of hydrogen on the wear of copper at room and elevated temperatures - Похмурський, В.І.; Василів, Х.Б.; Винар, В.А.; Арендар, Л.А. (Problems of Tribology, 2014)
The influence of gaseous and electrolytic hydrogenation on the tribological properties of technically pure copper is investigation. Shown that the tribological behavior of copper is determined by the chemical composition of surface friction, in particular, the presence or absence of oxide phases and plastic deformation micro protrusion of surface friction.